2016
DOI: 10.1016/j.marpetgeo.2016.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary heterogeneity and petrophysical characterization of Barremian tsunami and barrier island/inlet deposits: The Aliaga outcrop as a reservoir analogue (Galve sub-basin, eastern Spain)

Abstract: The present study examined two sandstone deposits in the Aliaga outcrop as a reservoir analogue over a distance of 200-m-long and attempted to establish a correlation between sand facies and the petrophysical properties of the sandstones in order to investigate the reservoir heterogeneity. The Aliaga reservoir analogue represents the upper part of Camarillas Fm., deposited during the Barremian synrift phase of the Galve sub-basin (Iberian Basin, Spain). It is characterized by a transitional sedimentary interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…10). Veloso et al (2016) showed the good correlation between the measured porosity and the sorting and cement facies (Fig. 11); facies were classified based on petrophysical characteristics determined from 27 plugs.…”
Section: Tsunami Reservoir Modelmentioning
confidence: 89%
See 3 more Smart Citations
“…10). Veloso et al (2016) showed the good correlation between the measured porosity and the sorting and cement facies (Fig. 11); facies were classified based on petrophysical characteristics determined from 27 plugs.…”
Section: Tsunami Reservoir Modelmentioning
confidence: 89%
“…The distribution of permeability and porosity values is strongly correlated with the facies distribution, principally in the b.i./inlet deposit, which were classified as a function of the sand sorting and cemented content. Thus, the spatial distribution of petrophysics values is controlled by the geometry of the depositional facies and the degree of continuity of sand bodies (Ambrose et al, 2008, Veloso et al, 2016.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations